Implementation of Interactive Poster-Based Learning: An Innovative Approach to Introducing Pancasila Figures to Grade 3 Students at Sukomulyo Elementary School - Wiwik Anita; Azamul Fadhly Noor Muhammad; Ari wibowo (Assyfa Learning Journal, 2026)
Background: Traditional teaching methods in Civic Education often lead to monotonous rote learning, preventing young students from grasping the essence of national heroes due to the lack of visually stimulating and interactive media. Objective: This study aims to develop an innovative QR code-based interactive poster media and evaluate its effectiveness in enhancing elementary students' competencies compared to conventional methods. Methods: Guided by the Research and Development (R&D) approach, this study designed a visual product integrated with independent digital content—including short animated videos, audio narratives, and interactive quizzes—accessible via smartphone scanning to measure cognitive, affective, and psychomotor learning domains. Results: The product achieved high theoretical validity scores of 86% from material experts and 84% from media experts. Empirical testing showed a significant leap in classroom performance, with the average score rising from 54.20 in the pre-test to 85.60 in the post-test, supported by a normalized gain (N-Gain) score of 0.68. Conclusion: The interactive poster serves as a highly valid, applicable, and practical tool that successfully transitions the learning paradigm into a student-centered environment, reduces understanding disparities, and fosters long-term competency development.